Exploring the Experiences of Senior High School Parents in Online Learning Context - Maglasang, Aya P.; Cruz, Fareeda De la; Gallardo, George Ryan B.; Tangkli, Khalid Yasper M.; Ea, Erich P. (Bumi Publikasi Nusantara, 2023)
As a remedy to the nearly shutting down of education owing to the spreading cases of COVID-19 all across the world, face-to-face classrooms where students could go to school were transitioned into online learning. As a result, parents are forced to help their children throughout their online learning. This study aims to explore and reveal the various experiences of Senior High School parents during online learning, how the transition from face-to-face learning to online learning affected their daily lives, and how the parents handled these changes. This qualitative study applied the Phenomenological Research design. Moreover, to analyze the data gathered, Thematic Analysis was utilized. The participants of the study were residents of the province of Sultan Kudarat, and parents whose child is enrolled in Sultan Kudarat State University – Laboratory High School, the Philippines. The participants were chosen through the Random sampling technique specifically the lottery method. According to the responses, parents have no choice but to support their children morally despite the differences in schedules inside the household. It was revealed that their children’s online learning serves as a distraction because they are having trouble balancing their time between performing their work and assisting in their children’s online learning. Moreover, the parents’ thoughts regarding e-learning vary depending on their situations. On the other hand, parents still believe that pursuing education in this time of pandemic will help their children to continue absorbing knowledge.